Disability and Human Dignity: Access to higher education as an insurmountable right - Gonzaga Monte da Costa, Danyelle; Medeiros , Lívia Laenny Vieira Pereira de; Souza, Paulo Zambrone de (The ESPecialist, 2024)
The thematic focus of this article is the inclusion of students with disabilities in higher education. The objective, through this work, is to verify the factors that can include and strengthen the permanence and learning of students with disabilities from their insertion with access to enrollment, their maintenance and permanence. The intervention proposal is through action research, of a descriptive type, as a means of enabling this group to participate in joint action in the training workshops. A process was carried out with the aim of transforming social reality through the educational process in higher education from the first-person perspective of students with disabilities and their experiences. During the process of preparing offices that can be applied to other universities that aim for inclusion and accessibility, even in the midst of architectural and attitudinal barriers that need to be resolved in the midst of recognizing the dignity of the human person inherent to everyone, subject as a subject of rights.